Impact of Integrating Rabies Education Into the Curriculum of Public Elementary Schools in Ilocos Norte, Philippines on Rabies Knowledge, and Animal Bite Incidence - Amparo, Anna Charinna B.; Mendoza, Eunice Charis B.; Licuan, Dianne A.; Valenzuela, Loida M.; Madalipay, Joye D.; Jayme, Sarah I.; Taylor, Louise H. (Frontiers in Public Health, 2019)
As part of a province wide rabies elimination program, rabies specific information was integrated into the curriculum of all public elementary schools in Ilocos Norte, Philippines using a specifically developed teachers’ manual. The rabies educational messages included rabies, animal bite prevention, bite management and responsible pet ownership and were integrated into lessons in several subjects. Four elementary schools were randomly selected and an assessment of the change in student’s rabies knowledge and animal bite incidence were conducted. The study tested all students in grades 1 to 5 before the curriculum integration was implemented and retested these cohorts one year later, after implementation. Awareness of rabies was high before the implementation, likely due to the province-wide elimination campaign. However, awareness still increased significantly across all schools, and detailed knowledge of rabies increased significantly in all but one school and age cohort. Bite incidence in the six months prior to each survey was also recorded and the percentage of students suffering animal bites fell significantly between the two tests. The data suggested that knowledge increase correlated with decreased bite incidence in some groups but not all, suggesting a more complex relationship between knowledge acquisition and behavioral change which warrants further investigation.